Association of cataract extraction and the risk of dementia—A systematic review and meta-analysis - Zhang, Qiao; Ju, Yuan; Zheng, Wei; Xie, Lulu; Wang, Xi; Ren, Huanhuan; Chen, Zhipeng; Liu, Xingtong; Bai, Xiaolin; Fan, Ruile (Frontiers in Aging Neuroscience, 2023)
Objectives This research aims to investigate if cataract extraction lowers the risk of all-cause dementia. Methods Original literature on cataract surgery associated with all-cause dementia as of November 27, 2022, was searched in several commonly used databases. Manual review was used to include eligible studies. Stata software (version 16) was used to perform statistical analysis on pertinent data. Publication bias can be precisely evaluated using funnel plots and Egger's test. Results In the meta-analysis of 4 cohort studies with 245,299 participants. Pooled analysis indicated that cataract surgery was linked to a lower incidence of all-cause dementia (OR = 0.77, 95%CI: 0.66–0.89; I2= 54.7%; P < 0.001). Cataract surgery was linked to a lower risk of AD (OR = 0.60, 95%CI: 0.35–1.02; I2= 60.2%; P < 0.001). Conclusions Cataract surgery is linked to a lower incidence of all-cause dementia and Alzheimer's disease. A cataract is a reversible visual impairment. Cataract surgery may be a protective factor against the onset of all-cause dementia and can reduce the economic and family burden caused by all-cause dementia worldwide. Given the restricted pool of included studies, our findings necessitate meticulous interpretation. Systematic review registration http://www.crd.york.ac.uk/prospero retrieve registration details by searching CRD4202379371.